The Role of Interest Rate in Moderating The Effect of Financial Risk On Financial Performance in Indonesia Banks List on The BEI - Mulyati, Mulyati; Widhiastuti, Susanti (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2024)
In this study, the effects of financial risk as measured by the Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Costs on Operating Income (BOPO), Loan to Deposit Ratio (DPR), and Net Interest Margin (NIM) on financial performance as measured by the Return to Asset (ROA) ratio are tested and examined for their moderating effects. additionally, the way in which LDR mitigates the impact of NPL on financial performance. During the years 2018–2023, this study was carried out at banking institutions that were listed on the Indonesia Stock Exchange. The sample acquisition technique in this observation uses the purposeful sampling method. Data obtained by visualizing secondary data obtained based on financial reports from the Indonesia Stock Exchange website at www.idx.co.id and banking company websites. The system utilized in this observation is descriptive quantitative, and statistical analysis data in this study were tested using partial least square and SEM with the help of Warp PLS 8.0. The study's findings show that while BOPO significantly negatively affects banking financial performance, CAR, NPL, LDR, and NIM have little effect on that performance. However, interest rates can mitigate the effects of LDR and NIM on the financial performance of banking companies. And interest rates cannot moderate the impact of CAR, NPL and BOPO on banking financial performance. While NPL has a positive effect on LDR , LDR cannot mediate the effect of NPL on banking financial performance.